2014
DOI: 10.1021/jp4114199
|View full text |Cite
|
Sign up to set email alerts
|

Recent NH3-SCR Mechanism Research over Cu/SAPO-34 Catalyst

Abstract: The preliminary mechanism research of NH3-SCR and NH3 oxidation over Cu/SAPO-34 catalyst is explored. The XRD, SEM, in situ EPR, NH3-SCR, NH3 oxidation test, DRIFTs, and the kinetic tests were performed for the bulk characterization, catalytic activity measurement, and the mechanism estimation. The NH3-SCR result showed that Cu/SAPO-34 revealed excellent activity during 120–600 °C, while the NH3 oxidation appeared above 300 °C and caused the decline of NO conversion. The order of various reactants (NO, NH3, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(110 citation statements)
references
References 27 publications
(66 reference statements)
10
98
1
Order By: Relevance
“…NH 3 -SCR activities are reduced a lot only at a high content of potassium (2.5% of potassium). Some authors [20,38,49] reported that at high temperatures Brønsted acid sites existed as ammonia storage sites and offered activated ammonia for the active sites in the NH 3 -SCR on the Cu-SAPO-34 catalyst, since ammonia could no longer adsorb on the active sites. However, ammonia still can adsorb on the isolated Cu + on the Cu-SAPO-34 catalyst at high temperatures (>300 °C), which can be observed in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NH 3 -SCR activities are reduced a lot only at a high content of potassium (2.5% of potassium). Some authors [20,38,49] reported that at high temperatures Brønsted acid sites existed as ammonia storage sites and offered activated ammonia for the active sites in the NH 3 -SCR on the Cu-SAPO-34 catalyst, since ammonia could no longer adsorb on the active sites. However, ammonia still can adsorb on the isolated Cu + on the Cu-SAPO-34 catalyst at high temperatures (>300 °C), which can be observed in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a consensus from a few recent studies that molecular NH 3 adsorbed on Cu ion sites is substantially more reactive than NH 4 + stored at Brønsted acidic sites. 20,27,37 It is further argued that molecular NH 3 adsorbed on other Lewis acid sites also contribute more than NH 4 + in the low-temperature regime. 20 Note specifically that fresh and HTA Cu,Ca/SSZ-13 samples show essentially no difference in SCR performance at low reaction temperatures.…”
Section: Cocation Effects On Scrmentioning
confidence: 99%
“…The mechanism of the SCR reaction had been studied extensively elsewhere and different hypotheses had been proposed (Li et al, 2011;Zhou et al, 2011;Fu et al, 2014;Yu et al, 2014). Fig.…”
Section: Discussionmentioning
confidence: 99%